Small Islands Mineral Mining Licensing Disharmony and the Ministry of Marine Affairs and Fisheries’ Authority - Ade Santi Irawati; M. Rizqi Akbari; Shinta Hadiyantina; Anindita Purnama Ningtyas (Universitas Sriwijaya, 2026)
Small islands in Indonesia possess unique ecological characteristics yet are highly vulnerable to the destructive impacts of extractive industries, particularly mineral mining. Although the legal regime under Law Number 27 of 2007 concerning the Management of Coastal Areas and Small Islands and its amendments (UU PWP3K) adopts a conservation paradigm, reality demonstrates a massive issuance of Mining Business Licenses (IUP) in these regions based on the regime of Law Number 4 of 2009 concerning Mineral and Coal Mining and its amendments (UU Minerba). The primary issue lies in the regulatory disharmony following the enactment of the Job Creation Law and the implementation of the Online Single Submission Risk-Based Approach (OSS-RBA) system, which systematically curtails the authority of the Ministry of Marine Affairs and Fisheries (KKP) as the guardian of coastal ecosystems. This research aims to examine the juridical implications of current licensing regulations for the principle of small island protection and to formulate measures to strengthen the KKP's authority. This study constitutes normative legal research utilising statutory and conceptual approaches. The results indicate that the current licensing system suffers from norm degradation by disregarding the standing of the UU PWP3K as lex specialis, as affirmed in Supreme Court Decision Number 403 K/TUN/TF/2024 and Constitutional Court Decision Number 35/PUU-XXI/2023. The absence of the KKP's substantive role results in the loss of ecological checks and balances mechanisms. This study concludes that the state must restore the KKP's authority by establishing technical regulations that make the Minister of Marine Affairs and Fisheries' recommendation an absolute prerequisite (conditio sine qua non) for the issuance of an IUP by the relevant agencies, thereby guaranteeing legal certainty and environmental sustainability.